The Early Modern Dutch Press in an Age of Religious Persecution The Making of Humanitarianism - de Boer, David (Oxford University Press, 2023)
For victims of persecution, attracting international awareness of their plight is often a matter of life and death. This book uncovers how in seventeenth-century Europe, persecuted minorities first learned how to use the press as a weapon to combat religious persecution. To mobilize foreign audiences, they faced an acute dilemma: how to make people care about distant suffering? This study argues that by answering this question, they laid the foundations of a humanitarian culture in Europe. The book reveals how, as consuming news became an everyday practice for many Europeans, the Dutch Republic emerged as an international hub of printed protest against religious violence. It traces how a diverse group of people, including Waldensian refugees, Huguenot ministers, Savoyard officeholders, and many others, all sought access to the Dutch printing presses to raise transnational solidarity for their cause. By examining their publicity strategies, this study deepens our understanding of how people tried to confront the specter of religious violence that had haunted them for generations.